2014
DOI: 10.1080/07328303.2014.977909
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fmoc-Thr Unit Carrying Core 1O-Linked Sugar With Acid-SensitiveO-Protecting Group and Its Application to the Synthesis of Glycosylated Peptide Thioester

Abstract: Y. Asahina et al.We newly designed and synthesized a 9-fluorenylmethoxycarbonyl (Fmoc)-threonine unit carrying the core 1 O-glycan, which is protected by the 4-methylbenzyl (MBn) group. This protection tactic enabled not only efficient assembly of glycoamino acid derivatives but also one-step deprotection by trifluoroacetic acid (TFA) after the Fmocsolid-phase peptide synthesis (SPPS). The usefulness of this unit was demonstrated by the Fmoc-SPPS of peptide thioester using the N-alkylcysteine (NAC)-assisted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…As a result, the reaction efficiently proceeded within four days (see Figure SI7 in the Supporting Information) and the desired peptide thioester 4 was obtained in 18 % yield based on the initial resin. The N‐terminal aryl thioester (1‐27) carrying the disaccharide 5 was synthesized using the NAC method as previously reported16 in a yield of 11 % (see Scheme SI4 and Figure SI8 in the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the reaction efficiently proceeded within four days (see Figure SI7 in the Supporting Information) and the desired peptide thioester 4 was obtained in 18 % yield based on the initial resin. The N‐terminal aryl thioester (1‐27) carrying the disaccharide 5 was synthesized using the NAC method as previously reported16 in a yield of 11 % (see Scheme SI4 and Figure SI8 in the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…We have recently demonstrated that the use of substituted‐benzyl protecting groups, instead of the Bn group, achieves a one‐step deprotection at the end of the SPPS, eliminating the problem of the low‐TfOH treatment . In particular, 4‐methylbenzyl (MBn) group is stable enough to the conditions required for the assembly of oligosaccharides, but sensitive to acid for the final deprotection using a TFA cocktail ,. Based on these results, we examined the extension of the MBn protection strategy for the carboxy‐ and hydroxy‐protection of sialic acid.…”
Section: Figurementioning
confidence: 99%
“…Based on previous results,, we first attempted the use of the MBn group as a protecting group for both the hydroxy and carboxy groups of sialic acid. The synthesis of sialylglycoamino acid 1 is shown in Scheme .…”
Section: Figurementioning
confidence: 99%
“…Thecarboxylic acid seems to participate in the N-to-S acyl shift reaction and enhance the overall rate of thioesterification reaction. TheN-terminal aryl thioester (1-27) carrying the disaccharide 5 was synthesized using the NACm ethod as previously reported [16] in ayield of 11 %(see Scheme SI4 and Figure SI8 in the Supporting Information). As aresult, the desired peptide thioester with MESNa was successfully obtained (see Figure SI6 in the Supporting Information).…”
mentioning
confidence: 99%
“…As ar esult, the reaction efficiently proceeded within four days (see Figure SI7 in the Supporting Information) and the desired peptide thioester 4 was obtained in 18 %y ield based on the initial resin. TheN-terminal aryl thioester (1-27) carrying the disaccharide 5 was synthesized using the NACm ethod as previously reported [16] in ayield of 11 %(see Scheme SI4 and Figure SI8 in the Supporting Information). Scheme 1.…”
mentioning
confidence: 99%